The World's Exposition March - Matilda Eidt::::::::: (Will Louis Music Publisher)
Piano score, 3 p. On cover is photo of Eddy Hanson, master organist of radio, and Grace Wilson, radios beloved personality, W.C.F.L. Chicago. Publishers advertisement on verso of last leaf.